Is Maximal Dosage for Local Anesthetics Taught Consistently Across U.S. Dental Schools? A National Survey. Issue 6 (1st June 2018) - DeLuke, Dean M.; Cannon, Darriel; Carrico, Caroline; Byrne, B. Ellen; Laskin, Daniel M.
Abstract : Administration of safe and effective local anesthesia is a cornerstone of dental practice, but there is some discrepancy in recommendations for maximum doses, with the Council on Dental Therapeutics and American Academy of Pediatric Dentistry's guidelines differing from the guidelines of manufacturers and contemporary textbooks. The aim of this study was to determine the level of uniformity across U.S. dental schools in teaching maximal safe doses for commonly used local anesthetics. Faculty members primarily responsible for teaching local anesthesia to dental students at all 62 U.S. dental schools that had graduated classes were invited to participate in a survey in March 2017. The survey included questions about maximum doses taught, awareness of the existence of two differing guidelines, and whether one or both guidelines were commonly taught to students. A total of 37 responses were received, for a response rate of 60%. The respondents included oral and maxillofacial surgeons, general dentists, dental anesthesiologists, and periodontists. Of the respondents, 22% reported being unaware of the existence of more than one standard, and there was inconsistency in teaching practices. A majority (73%) reported teaching the higher maximum dose (7 mg/kg) for lidocaine, while a similar but smaller majority (60%) reported teaching the lower dose threshold (4.4 mg/kg) for mepivacaine. This study found no standard recommended maximum dose of lidocaine or mepivacaine being taught in U.S dental schools. Students should be made aware that there is more than one standard, and teaching should emphasize sound medical and pharmacologic principles. There is also a need to ensure that questions on dental licensing examinations are consistent regarding maximum safe doses for local anesthesia.